Differentiation-dependent alterations in histone methylation and chromatin architecture at the inducible chicken lysozyme gene - Lefevre, Pascal; Lacroix, Claire; Tagoh, Hiromi; Hoogenkamp, Maarten; Melnik, Svitlana; Ingram, Richard; Bonifer, Constanze (The Journal of biological chemistry, 2005)
It is now well established that locus-wide chromatin remodeling and dynamic alterations of histone modifications are required for the developmentally regulated activation of tissue-specific genes. However, little is known about the dynamics of these events during cell differentiation and how chromatin of an entire gene locus responds to signal transduction processes. To address this issue we investigated chromatin accessibility, linker histone distribution, and the histone methylation status at the macrophage-specific chicken lysozyme locus and the ubiquitously expressed gas41 locus in multipotent precursor cell lines and BM2 monoblast cells. The latter can be induced to go through macrophage maturation by treatment with phorbol-12-myristate acetate and can be further stimulated with bacterial lipopolysaccharide. We show that expression of the lysozyme gene in undifferentiated monoblasts is low and that a high level of gene expression requires both cell differentiation and lipopolysaccharide stimulation. However, depletion of the linker histone H1 is observed already in lysozyme non-expressing multipotent precursor cells. In undifferentiated monoblasts, the lysozyme regulatory regions are marked by the presence of monomethylated histone H3 lysine 4, which becomes increasingly converted into trimethylated H3 lysine K4 during cell differentiation. We also present evidence for extensive, differentiation-dependent alterations in nuclease accessibility at the lysozyme promoter without alterations of nucleosome and transcription factor occupancy.